(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
This article is intended to analyse the Teatro, As A Representation of the conflicts of the self and its relationship with the world. Search the Through the actors–the characters, the Other being no more than the Self, evidencer A Concienc Cultural heritage in a Show society. The Research focuses on the theatre of Gustavo Ott, for whom The Show is la Alteridad of contemporary SocietyTheir Dramatic works Pose in the subject and staging existential conflicts of man, as well as Violence, death, the Absurd, the dark, the cruelty And The humour. Therefore, the article intends to describe as the author merely aestheticised the violence and experiments in theatrical scenes with literature and cinema, using Theories and methods of La Alteridad of M. Bakhtin; La Sociedad of the Show, M. Vargas Llosa, The Cinema of Q. Tarantino, Through qualitative research, with analytical reading and extensive documentary records.